THE WAY SUNDANESE GIVE NAMES TO THEIR BABY: CULTURAL ANTHROPOLOGY VIEW IN ETHNOMATHEMATICAL STUDIES - Eko Yulianto; Muhamad Zulfikar Mansyur; Iyus Jayusman; Zulpi Miftahudin (Program Studi Magister Pendidikan Matematika, Universitas Siliwangi, 2022)
The mystery of numbers that were considered to have a role in the mystical dimension has long been practiced since the time of Pythagoras, then known as numerology. Some people in Sundanese tradition believe that numerology brings a lucky influence on their lives and generations. This study aims to reveal how the Sundanese tradition of naming their newborn babies and conduct a phenomenological study on several respondents with unique experiences related to Sundanese numerology in their names. The phenomenon experienced by respondents is seen from the point of view of cultural anthropology. This research was designed using qualitative methods through two approaches, ethnomathematics and phenomenology. Respondents were selected using purposive sampling and snowball methods and obtained 25 respondents scattered around the districts of Ciamis, Banjar, Tasikmalaya, and Garut in West Java. All respondents are expert resources as cultural practitioners in their own culture who can explain the numerology system they used, known as Kasepuhan. The results of the study show that there are many different numerological methods for calculating